Innovation and employment in Sub-Saharan Africa - Porath, Daniel,Nabachwa, Sarah,Agasha, Ester,Kijjambu, Nsambu Frederick (University of Applied Science Mainz, 2021)
The debate on the role of innovation in employment growth is still inconclusive with the available literature focusing largely on industrialised economies. With this concern, we examine the potential of innovations in creating permanent full-time jobs in registered manufacturing companies in Sub-Saharan Africa (SSA) by fitting the model of Van Reenen (1997) to a two-period panel of 687 manufacturing firms. Our paper is the first to examine the impact of innovation on employment with a particular focus on SSA and the first to apply a panel data approach to a larger set of developing countries. Our findings indicate that in the past, innovative firms created more jobs compared to non-innovative ones when controlling for sales, wages, time-invariant firms and country specifics. Likening the results with emerging or developing economies outside of SSA, we find that the effect is considerably larger in SSA than in other regions. As a consequence, we recommend that SSA governments strengthen their technological adaption and adoption mechanisms in their manufacturing sectors to foster innovations. Nonetheless, as a way to discourage imitations (which may not be well aligned to the production demands in SSA), governments are encouraged to invest in sector-specific research and development.
10419/235646
Keywords: Graue Literatur; Innovation; Employment; Sub Saharan Africa; Panel model; Enterprise Survey